TECHNOLOGICAL DEVELOPMENT IN SOYBEAN PRODUCTION AND ITS IMPACT ON LABOR IN THE SOUTH OF GOIÁS STATE, BRAZIL DESENVOLVIMENTO TECNOLÓGICO NA PRODUÇÃO DE SOJA E SEU IMPACTO SOBRE O TRABALHO NA REGIÃO SUL DE GOIÁS - Caroline Sales Arruda; Sônia Milagres Teixeira (Pesquisa Agropecuária Tropical, 2010)
<!-- @page { margin: 2cm } P { margin-bottom: 0.21cm } --> The expansion of soy production in the Goiás State has caused changes in its agricultural productive structure. However, besides bringing economical progress, the adoption of the technology imposed by capital resulted in changes in the social relations of production and labor. The study has focused on the analysis of social costs, specifically referring to labor, applied to technological development in agriculture, on the South of Goiás State, Brazil. So, factorial analysis was used, making it possible to identify the municipalities that use technology in the most and least intensive way. The study reveals that the municipalities with higher indexes of technology use are Rio Verde, Jataí, Catalão, Morrinhos, and Piracanjuba, due to an increasing process of migration from rural properties to cities, decreasing of workplaces on farming and loss of life quality to farmers and their families. KEY-WORDS: Factorial analysis; agriculture modernization; technology. <!-- @page { margin: 2cm } P { margin-bottom: 0.21cm } --> A expansão da soja, no Estado de Goiás, provocou mudanças na estrutura produtiva agrícola. Se, por um lado, possibilitou avanço econômico, por outro, a adoção de tecnologias impostas pelo capital resultou em mudanças nas relações sociais de produção e trabalho. O estudo teve como foco principal a análise de custos sociais, especificamente no que se refere ao trabalho a que o desenvolvimento tecnológico na agricultura da mesorregião Sul Goiano se submete. Para tanto, foi utilizada a análise fatorial, que possibilitou identificar os municípios mais e menos intensivos no uso de tecnologias. O estudo revela que os municípios que mais se destacam, com alto índice de utilização de tecnologias, são Rio Verde, Jataí, Catalão, Morrinhos e Piracanjuba, devido a um crescente processo de migração da população do campo para as cidades, diminuição de postos de trabalho na agropecuária e perda na qualidade de vida das famílias de proprietários de terra. PALAVRAS-CHAVE: Análise fatorial; modernização da agricultura; tecnologia.